Research of the system of information providing for safe pharmacotherapy pregnancy in the world - N. M. Maksymovych; I. G. Mudrak; O. M. Zaliska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Improvement of information provision for safe and rational use of medicines at pregnancy is a priority task for all system of healthcare in the world. The purpose of this study was to analyze and carry out a systematic analysis of information sources, databases, registries operating on the international, state, professional levels on the safe use of medicines, including duration pregnancy in the countries of the world. Summarized recommendations, directives of the World Health Organization about safety of pharmacotherapy, especially during pregnancy, and the need for improvement information provision for the appointment of drugs during pregnancy, since 50% and more pregnant women use more than 4 drugs. Systematized the main sources of information, a database of safe use of medicines during prеgnancy in Europe and the United States on professional levels, as well as specially for patients. The directions of the real word data collection were shown and made the establishment of registries of pregnant women taking medications that allow monitoring of adverse reactions during pregnancy. The modern trends on improving information provision by Food and Drug Administration (FDA) also for instructions and labeling of drugs depending on the risk category of pregnancy were presented. The use of modern information sources, databases, patient registries is relevant to provision of rational use of medicines, especially for pregnant women in Ukraine.